Falsification, Annual Targets, and Errant Leadership: Media Portrayal of the Atlanta Test-Cheating Scandal. (November 2015) - Freeman, Eric
This analysis of the Atlanta test-cheating scandal differs markedly from the version reported in the press. Using discourse analysis, I examined over 50 articles published in the Atlanta Journal-Constitution ( AJC ), the hometown newspaper at the center of the investigation. Because newspapers are a primary source of information, the AJC 's discursive framing of test-tampering and systemic wrongdoing was a powerful voice in shaping how the public understood what happened. But failure to situate the scandal in a context of economic deprivation and residential segregation while omitting discussion of the damaging cognitive and academic effects that stem from living in distressed neighborhoods meant the AJC depicted a misleading version of events. Although the school district has recovered, the inequalities which fomented the crisis remain intact. I revisit the Atlanta Compromise of 1973 to conclude that as in the past, a policy of schools alone is an insufficient corrective for educational disadvantage.